Are Motor Control and Regulation Problems Part of the ASD Motor Profile? A Handwriting Study. Issue 7 (3rd October 2018) - Grace, Nicci; Johnson, Beth P.; Rinehart, Nicole J.; Enticott, Peter G.
ABSTRACT: The primary aim of this study was to kinematically assess how children with autism spectrum disorder (ASD) plan and control their handwriting actions. Forty-three boys aged between 8 to 12 years were included in the present analysis; 23 with ASD and 20 typically developing (TD) controls. Sophisticated objective and quantifiable assessment of movement metrics and dynamics was applied across a series of basic cursive handwriting sequences. Children with ASD demonstrated atypical control of handwriting metrics and dynamics, as well as significantly greater neuromotor noise relative to age-matched peers. They also engaged in less regular monitoring and regulation of their movement during the handwriting task. This study provides new insights into the way children with ASD plan and sequence their handwriting movements. Overall, results revealed that even at a basic level, children with ASD appear to have a breakdown in their ability to control and regulate their handwriting movements. This has important implications for the school-aged child who constantly engages in handwriting tasks within the classroom environment and provides insight into possible directions for future intervention.